2019
DOI: 10.1186/s13643-019-1210-6
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated models of service delivery for antiretroviral treatment of HIV in sub-Saharan Africa: a rapid review protocol

Abstract: BackgroundTo meet global targets for the treatment of HIV, high-prevalence countries are launching or expanding differentiated models of service delivery (DSD) for antiretroviral therapy (ART). Ongoing studies report on metrics specific to individual models of care, but little is known about the overall scale, impact, costs, and benefits of widespread implementation of DSD. We will conduct a rapid review of recent literature on DSD currently in use in sub-Saharan Africa and identify gaps in the literature with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…Following World Health Organization guidance for rapid reviews [6], we conducted a rapid systematic review of peer‐reviewed publications and conference abstracts that reported outcomes of differentiated service delivery (DSD) models for the provision of antiretroviral treatment (ART) in sub‐Saharan Africa since 2016 [7]. The search protocol was previously presented [7], and the review was registered on the International Prospective Register of Systematic Reviews (PROSPERO CRD42019118230).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following World Health Organization guidance for rapid reviews [6], we conducted a rapid systematic review of peer‐reviewed publications and conference abstracts that reported outcomes of differentiated service delivery (DSD) models for the provision of antiretroviral treatment (ART) in sub‐Saharan Africa since 2016 [7]. The search protocol was previously presented [7], and the review was registered on the International Prospective Register of Systematic Reviews (PROSPERO CRD42019118230).…”
Section: Methodsmentioning
confidence: 99%
“…In this report we focus on these outcomes only, to allow for a more detailed examination and discussion of consistently defined indicators. The full report of the review is available online [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of studies have evaluated the acceptability and clinical outcomes of DSD models [ 6 , 7 ], current evidence on the cost and cost-effectiveness of commonly implemented DSD models is limited [ 8 ]. There have been no published studies of patient-level healthcare resource utilization or provider costs for any DSD model of care in Zambia.…”
Section: Introductionmentioning
confidence: 99%
“…Given the numerous options for how and where to make improvements to HIV services, identifying which service features are most important to PLWH can aid future intervention design and prioritization. Differentiated services delivery models which aim to deliver more patient-centered services by varying several aspects of service delivery in Sub-Saharan Africa, such as visit frequency, waiting time, and service location, have to date shown modest effects on treatment outcomes [2,11], suggesting that more needs to be considered to improve engagement in HIV care. These models have been informed by the need to decongest health services and a wealth of research identifying barriers to HIV care including: competing work and family priorities, economic costs, stigma, overburdened and incoordinate health services, and disrespectful health workers [12][13][14].…”
Section: Introductionmentioning
confidence: 99%